Implementasi kebijakan pengangkatan tenaga guru honorer menjadi pegawai pemerintah dengan perjanjian kerja (pppk) di kota palembang - Marto, L. Syaidiman; Mayseni, Boditta; Mawaddah, Mawaddah; Franchika, Tri Mulia; Muslim, Muslim (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
For the successful implementation of the Honorary Teacher Appointment Policy in Palembang City, the commitment of organizational leaders is required to be optimal in all stages of activities and more intensive coordination with related parties. For this reason, it needs to be supported by a proportional budget for each activity stage. In addition, it must also be supported by adequate personnel and capacity building. This can be done, for example, through training, especially those related to planning and evaluation. The appointment of honorary staff has created problems within government agencies. The policy of Government Regulation (PP) Number 49 of 2018 concerning PPPK Management is expected to resolve these problems. This research uses qualitative research methods with descriptive analysis; data is collected through observation, in-depth interviews, and documentation. The research location is Palembang City. From the results of the study, it was found that the Implementation of Policy on the Appointment of Teachers to become government employees with work agreements (PPPK) in Palembang City has not been implemented properly; this can be seen from the reality in the field that there are still many honorary teachers who have not yet been appointed as civil servants or become government employees with work agreements (PPPK), this is because the variables of policy standards and objectives, resources, organizational characteristics, and the implementation of PPPK are not well implemented.